Clinical impact of a pharmacist-physician co-managed programme on hyperlipidaemia management in Hong Kong - Lee, V. W. Y.; Fan, C. S. Y.; Li, A. W. M.; Chau, A. C. Y. (Journal of clinical pharmacy and therapeutics, 2009)
Summary Objective:  The study aimed to investigate the clinical impact of pharmacist–physician co‐managed programme on the management of hyperlipidaemia. Methods:  The study was a prospective randomized controlled trial. Adult patients were selected if: (i) they were taking one or more lipid‐lowering agents with a valid lipid panel before their next follow up; (ii) had a baseline lipid profile within the previous 6 months; (iii) their lipid panel did not reach the targeted low‐density lipoprotein‐cholesterol (LDL‐C) goal based on the National Cholesterol Education Programme Adult Treatment Panel III. Pharmacists interviewed patients in the intervention group for 15–30 min to provide consultation on the drug regimen and lifestyle modifications. A telephone follow‐up every 4 weeks and a follow‐up interview on the date of the physician visit were scheduled. Patients in the control group received routine conventional care. The primary outcome measurement was the change in lipid panel between baseline and at the end of study. Results:  One hundred and eighteen patients were recruited to the study [58 patients in intervention group (mean age 63 ± 10 years old) and 60 in control group (mean age 61 ± 12 years old)]. Starting with similar baseline levels, the end of study LDL‐C and total cholesterol levels for the intervention and control groups were LDL‐C: 2·80 ± 0·89 mmol/L and total cholesterol 4·75 ± 1·08 mmol/L vs. LDL‐C: 3·24 ± 0·78 mmol/L and total cholesterol 5·18 ± 0·93 mmol/L, respectively. The differences were statistically significant (P < 0·0015). Conclusion:  The study showed that a pharmacist–physician co‐managed programme for hyperlipidaemic patient was effective in getting more patients to reach their target lipid levels.